Gender, body, and archive in the work of Mariona Giner1. Issue 2 (June 2019) - Titus, Anna
Abstract : This article sets out to explore a series of works by Catalan documentary photographer Mariona Giner in order to reveal how her practice explicitly addresses the performance of gender in the archive. Beginning with a brief overview of her work and of the question of gender in the archive, I go on to discuss the representation of subalternity in the photographic archive before situating Giner's work in relation to the more classificatory, objectifying, and exclusionary practices historically identified with the production of archival knowledge. By looking at how the bodies of women, their emotions, and feelings are represented in three photographic series – Relats curts de la Mina, Públic/Privat, and Wad/Ras'92 – I aim to reveal the ways in which Giner's practice challenges the dialectic between public and private, mind and body, discursive and performative, instituted by the archive, through the relational production and display of the photographic image.